Lab manual for A+ guide to managing and maintaining your PC - Andrews, Jean (Course Technology, 2003)
This Lab Manual is designed to accompany any of the A+ Guides and provides additional hands-on practice need to succeed in industry. This Lab Manual is also an excellent resource to use to prepare for CompTIA's 2003 A+ certification exams